GI-4000 in KRAS mutant cancers. (February 2014) - Shahda, Safi; O'Neil, Bert
<x xml:space="preserve">Abstract</x> Introduction: Cancer develops mainly as a result of accumulating mutations in genes controlling cell growth regulation. RAS is one of the most commonly mutated genes in cancer. While agents targeting the signaling aspects of RAS have met with some success, resistance to therapy remains a major issue. Another focus of drug development has been to harness the immune system to target cells harboring mutated proteins, which can appear 'foreign' to the immune system. It has been observed that cancer is able to avoid regular immune surveillance through local and systemic mechanisms leading to immune tolerance. One potential way of breaking immune tolerance is through vaccine therapy. Areas covered: The authors review the current but limited available literature on KRAS vaccine therapy. The research reviewed was identified from PubMed and presentations from national oncology meetings related to KRAS vaccines in general and <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=GI-4000&logicalOpe1=OR&field2=articletitle&text2=GI-4000&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">GI-4000 series specifically. Expert opinion: While targeting KRAS has proven difficulties, developing novel vaccine approaches such as 'tarmogens' appear to be safe with early efficacy in subset of patients with KRAS mutations. However, further research is crucial to identify this group of patients and develop biomarkers.